If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5n+2(3n-5)=8n-1
We move all terms to the left:
5n+2(3n-5)-(8n-1)=0
We multiply parentheses
5n+6n-(8n-1)-10=0
We get rid of parentheses
5n+6n-8n+1-10=0
We add all the numbers together, and all the variables
3n-9=0
We move all terms containing n to the left, all other terms to the right
3n=9
n=9/3
n=3
| 4n-8=-4n | | -3c+10-6-2c=14 | | -5+12n=18n+7 | | 5(x-7)+19=2(x-5) | | -1000=x=8 | | 0.03t+0.08/0.7=0.2 | | 3x^2+30x+77=0 | | 8z-34+3z=8z+15 | | 00.8x+.72=2.4 | | 15k=25 | | 7x+42=-42 | | (3/5)X(5x+15)=-12 | | 1431=15.25x+25 | | 8z-34+3z=8z-15 | | 40.25=13.75+2x | | 7=2-3+4z | | X+x+1+x+2+x+3=262 | | 11a+5a-8a-3a=15 | | 6(h+20)=240 | | 4z^2-24+10z=0 | | -2x+3(3x+11)=-23 | | 3(x+5)-6=5x+1 | | -42+6y=-42 | | c-40+c-45=c+24 | | -36=9-9x | | 5x+4(x-1)=2+5(x+2) | | 3x-7(6-x)=3 | | -9x-5x=9 | | -10m+-10=60 | | u/5+3=8 | | 187=7x+3(-6x+22) | | (-4x+70)=-2+4x |